Potassium tert-Butoxide Mediated O-Arylation of N-Hydroxyphthalimide and Oximes with Diaryliodonium Salts - Misal Castro, Luis C.; Chatani, Naoto (Synthesis, 2014)
A metal-free method for the direct O-arylation of N-hydroxyphthalimide, pyridine-2-carboxaldehyde oxime, acetophenone oxime, or dimethylglyoxime with diaryliodonium salts under mild reaction conditions and short reaction time in the presence of potassium tert-butoxide is reported. The diaryliodonium counterion salt plays an important role in the reaction when it is carried out at 40 °C or lower temperatures.
Keywords: O-arylation; O-arylhydroxylamines; oximes; N-hydroxyphthalimide; diaryliodonium salts